Additive manufacturing of nylon composites with embedded multi-material piezoresistive strain sensors for structural health monitoring - Gackowski, Bartosz Mikolaj (2023)
A hybrid additive manufacturing process is proposed to incorporate piezoresistive sensors into a polyamide matrix for real-time structural health monitoring. 3D-printed samples were tested under tensile, flexural, and indentation testing using various sizes, numbers, and locations of the sensors, while the electrical resistance was recorded in real-time. Under uniaxial tensile loading, strength reached 36 MPa, and the resistance values linearly increased by up to 105% at ∼150% of strain. During flexural testing, the sensor had higher resistance when it was located above the supports rather than under the loading roller. The conductive paths were placed near the plate's top, middle and bottom sections to localise the damage during indentation testing. The energy absorbed during indentation testing reached 34–36 J. Resistance readings of sensors with 1 cm width showed better linearity and sensitivity than their wide (10 cm) counterparts. Three 2D sensors were interconnected to make a 3D sensor. The resistance values gradually increased after each strike during repeated indentation, but the overall strength remained similar. In summary, this work demonstrates a novel approach toward customisable 3D-printed piezoresistive sensors for detecting global or local damage.